Photoreforming of food waste into value-added products over visible-light-absorbing catalysts. Issue 10 (6th May 2020) - Uekert, Taylor; Dorchies, Florian; Pichler, Christian M.; Reisner, Erwin
Abstract : Food and mixed wastes are converted into H2 and organics over CdS and carbon nitride photocatalysts. Abstract : Approximately 1.3 billion tons of food waste are generated each year, resulting in societal, economic and environmental repercussions across the globe. While efforts to minimise losses and redistribute resources are underway, vast quantities of food waste must still be managed. Photoreforming offers a simple, sunlight-driven method for transforming food waste into valuable chemicals and clean H2 fuel, but the minimal previous research on this topic relied on expensive and UV-absorbing catalysts. Here, we utilise two precious-metal-free and visible-light-driven photocatalytic systems (CdS quantum dots in alkaline solution and carbon nitride with co-catalyst Ni2 P under pH neutral conditions) to photoreform a variety of carbohydrates, fats, proteins and real-world mixed wastes into H2 and organic products such as formate. CdS offers higher efficiencies in alkaline media than a benchmark TiO2 |RuO2 -Pt catalyst, but carbon footprint calculations suggest that photoreforming with carbon nitride|Ni2 P in pH neutral H2 O offers a more sustainable route towards real-world application.